"Masked" Lewis-acidity of an aluminum α-phosphinoamide complex. Issue 11 (28th February 2017) - Zijlstra, Harmen S.; Pahl, Jürgen; Penafiel, Johanne; Harder, Sjoerd
Abstract : An aluminum complex with a bulky α-Ph2 P-amide ligand is not sufficiently Lewis-acidic for activation of Cp*2 ZrMe2 but reacts irreversibly as an Al/P FLP reagent with alkenes and other unsaturated substrates. Abstract : The reaction of Ph2 P(DIPP)NH with AlMe3 cleanly gives an aluminum amide complex that crystallizes as a centrosymmetric dimer with a six-membered Al–N–P–Al–N–P ring. In aromatic solvents the dimer remains intact but the Al–P bond is readily broken upon addition of THF to form Ph2 P(DIPP)NAlMe2 ·THF. Efforts to use [Ph2 P(DIPP)NAlMe2 ]2 as a "masked" Lewis acidic activator for olefin polymerization catalysts were unsuccessful but the complex showed a Frustrated Lewis pair reactivity instead. The P/Al complex reacts with isocyanates to give the CO inserted product that crystallizes as a five-membered ring system Al–O–C(NR)–P–N. The reaction of [Ph2 P(DIPP)NAlMe2 ]2 with CO2, however, gave an insertion in the N–Al bond and the dimeric product [Ph2 P(DIPP)NCO2 AlMe2 ]2 was isolated. The dimer [Ph2 P(DIPP)NAlMe2 ]2 is one of the few Al/P FLPs that can activate CC double bonds irreversibly. A reaction with allyl methyl sulfide and 1-hexene led to the clean formation of the structurally similar activated alkene products [(DIPP)N-Ph2 P-CH(CH2 SMe)CH2 ]AlMe2 and [(DIPP)N-Ph2 P-CH(C4 H9 )CH2 ]AlMe2 .